2015
DOI: 10.1039/c5pp00297d
|View full text |Cite
|
Sign up to set email alerts
|

Microwave discharge electrodeless lamps (MDELs). Part IX. A novel MDEL photoreactor for the photolytic and chemical oxidation treatment of contaminated wastewaters

Abstract: This article reports on the fabrication and enhanced performance of a novel microwave discharge electrodeless lamp (MDEL) consisting of a three layered cylindrical structure that was effective in the remediation of wastewater containing the 2,4-D herbicide and the near total sterilization of bacteria-contaminated pond water (E. coli and other microorganisms) through photolysis with the emitted vacuum-UV (185 nm) and UVC (254 nm) light from the MDEL and through chemical oxidation with reactive oxygen species (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
1
7
1
Order By: Relevance
“…Photolysis is carried out using the released vacuum ultraviolet light 185 nm , and chemical oxidation is carried out with the ROS generated by the photodecomposition of dioxygen and air oxygen in one of the photoreactors. We reported that this new MDEL is effective for the disinfection E. coli of water and the decomposition of 2,4-dichlorophenoxyacetic acid 2,4-D in water 16 . We have also reported that photocatalytic TiO 2 oxidation reaction significantly improved when the photocatalyst is simultaneously irradiated by microwaves and UV light 17 because electron transfer inside the TiO 2 photocatalyst is optically optimized by microwaves 18 .…”
mentioning
confidence: 93%
“…Photolysis is carried out using the released vacuum ultraviolet light 185 nm , and chemical oxidation is carried out with the ROS generated by the photodecomposition of dioxygen and air oxygen in one of the photoreactors. We reported that this new MDEL is effective for the disinfection E. coli of water and the decomposition of 2,4-dichlorophenoxyacetic acid 2,4-D in water 16 . We have also reported that photocatalytic TiO 2 oxidation reaction significantly improved when the photocatalyst is simultaneously irradiated by microwaves and UV light 17 because electron transfer inside the TiO 2 photocatalyst is optically optimized by microwaves 18 .…”
mentioning
confidence: 93%
“…Protocols typically used in such treatments involved mercury-type electrode lamps that were subsequently replaced by electrodeless discharge lamps (EDLs) as the light sources, which when placed inside a microwave field effectively produced UV-Vis radiation; they are referred to as MDELs. Such microwave discharge electrodeless light sources use simultaneously both UV and microwave radiations to degrade effectively organic compounds and destroy microorganisms often found in contaminated waters [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our research efforts reported previously have focused on novel MDELs that use advanced oxidation processes (AOPs) toward water treatment and air purification [6,8,9]. In some cases, these MDELs contained traces of mercury that posed some concerns to the environment with regard to Hg-toxicity exposure in the form of organic and inorganic mercury.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the removal of the antibiotic ciprofloxacin from water by microwave UV lamps was also conducted 17 . Besides, Horikoshi et al developed a novel microwave electrodeless UV lamp for the photolysis and chemical oxidation of contaminated wastewater 18 . However, the intensity of light varies with the distance to microwave source, and the intensity of ultraviolet radiation increases as shortening the distance.…”
Section: Introductionmentioning
confidence: 99%